Dinâmica, ocupação e impactos socioambientais na microbacia do rio do Sal - Bezerra, Givaldo Santos (2014)
In Brazil, environmental damage on water resources, and growing, are increasingly noticeable. This fact justifies the neglect in decades with the rivers and other waterways, which consequently ended up compromising the quality of these resources over time. Thus, in order to better elucidate the issues investigated, this study was, in general terms, to analyze the dynamics, occupation and socio-environmental impacts in the watershed of the Salt River, from the perspective of planning and land / environmental planning. In the investigation of the facts elucidated, it was decided to geossistêmica approach, since the division of the area in landscape units facilitates knowledge of the interactive society and nature processes, constituting an important tool for planning and environmental management. In this sense, were considered here the most relevant characteristics of nature and of the watershed area of society, through the taxonomic levels established by Bertrand, centering the analysis within the limits that the work schedule allowed. To fulfill the goals outlined, took into account the methodological proposal of Libault based on the four levels of geographical research (compilatório, correlative, semantic and normative). Among other results, it was found that the geosystem Coastal Plain is part of the landscape class Regressive with predominant degree of very strong human disturbance due to changes processed in your geographical area in the last decades of the twentieth century and beginning of this century, carried effect by the public sector and the private sector, especially with the urban growth of Aracaju in its northern sector and of Our Lady of Help with the construction of housing, mangrove landfills for allotment, real estate projects, industrial, among others. A striking feature of this unit is geosystemic vulnerability to disordered occupations, low geotechnical support to the existence of fragile ecosystems and legally protected locations where the current modeling proceeds intensive, and unstable mutant form. In geosystem Coastal Plains highlights were two landscape classes where one perceives the procedural dynamics in the relationship space-time use and land use in the watershed. The class of Progressive Landscape presents a behavior change in rural production structure, denouncing greater degree of intervention and expansion of land use, especially since 1980, and in landscape class Regressive the degree of human influence more strongly visible reserves to occupation of the northern districts of Aracaju. Therefore, according to the specifics of each municipality, the risk situations, problems, conflicts and social and environmental clashes require management and co-management strategies. In the case of specific watershed, it is imperative to install a mediation practice between the interests of various social actors and the potential or explicit conflict generated from the action on the environment of geosystems.